Hippokratesa z Chios kwadratura księżyczków - Wesoły, Marian A. (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
I dedicate this article, in Memoriam, to Professor Sylwester Dworacki, my first guide in Greek texts, with whom I later had the distinguished privilege to frequently discuss diverse issues in philological exegesis. The little-known figure of Hippocrates of Chios has recently attracted strong interest of several scholars, though mainly by historians of mathematics. Aristotle mentioned critically his quadrature of the circle by means of segments or by means of lunules. Aristotle’s commentator Simplicius, citing Eudemus of Rhodos, quoted a longer paraphrase of Hippocrates’ arguments regarding the quadrature of the lunules. Appropriately selected parts from these arguments are given here in Greek, along with their faithful Polish translation. One should carefully understand the critical stance of Aristotle, who in his particular way understood quadrature as the finding of the geometrical mean and, therefore, accused Hippocrates of using false diagrams.